THE GAME AS A TEACHING RESOURCE FOR STUDENTS WITH SPECIAL NEEDS - José M. Bautista-Vallejo; Isaac Garrido Gómez; Manuel J. Espigares-Pinazo (Universidad Nacional del Nordeste, 2018)
This paper discusses the benefits of practicing Physical Education for students with special educational needs, and the use of the game as a teaching resource to help these students to improve relations with others and promote their integration into classes Physical Education. On the other hand, it will reflect on the importance of sporting activities to consolidate equality and solidarity between disabled and non-disabled. In this work sporting activities and games will be grounded in the characteristics of different special educational needs.